Cold-Adapted Alanine Dehydrogenases from Two Antarctic Bacterial Strains: Gene Cloning, Protein Characterization, and Comparison with Mesophilic and Thermophilic Counterparts - Galkin, Andrey (American Society for Microbiology, 1999)
The genes encoding NAD(+)-dependent alanine dehydrogenases (AlaDHs) (EC 1.4.1.1) from the Antarctic bacterial organisms Shewanella sp. strain Ac10 (SheAlaDH) and Carnobacterium sp. strain St2 (CarAlaDH) were cloned and expressed in Escherichia coli. Of all of the AlaDHs that have been sequenced, SheAlaDH exhibited the highest level of sequence similarity to the AlaDH from the gram-negative bacterium Vibrio proteolyticus (VprAlaDH). CarAlaDH was most similar to AlaDHs from mesophilic and thermophilic Bacillus strains. SheAlaDH and CarAlaDH had features typical of cold-adapted enzymes; both the optimal temperature for catalytic activity and the temperature limit for retaining thermostability were lower than the values obtained for the mesophilic counterparts. The k(cat)/K(m) value for the SheAlaDH reaction was about three times higher than the k(cat)/K(m) value for VprAlaDH, but it was much lower than the k(cat)/K(m) value for the AlaDH from Bacillus subtilis. Homology-based structural models of various AlaDHs, including the two psychrotrophic AlaDHs, were constructed. The thermal instability of SheAlaDH and CarAlaDH may result from relatively low numbers of salt bridges in these proteins.